Mechanistic Understanding for the Greater Sensitivity of Monkeys to Antisense Oligonucleotide–Mediated Complement Activation Compared with Humans - Shen, Lijiang; Frazer-Abel, Ashley; Reynolds, Paul R.; Giclas, Patricia C.; Chappell, Alfred; Pangburn, Michael K.; Younis, Husam; Henry, Scott P. (The Journal of pharmacology and experimental therapeutics, 2014)
Differences in sensitivity of monkeys and humans to antisense oligonucleotide (ASO)–induced complement alternative pathway (AP) activation were evaluated in monkeys, humans, and in serum using biochemical assays. Transient AP activation was evident in monkeys at higher doses of two 2′-O-methoxyethyl (2′-MOE) ASOs (ISIS 426115 and ISIS 183750). No evidence of AP activation was observed in humans for either ASO, even with plasma ASO concentrations that reached the threshold for activation in monkeys. The absence of complement activation in humans is consistent with a query of the Isis Clinical Safety Database containing 767 subjects. The in vivo difference in sensitivity was confirmed in vitro, as monkey and human serum exposed to increasing concentrations of ASO indicated that monkeys were more sensitive to AP activation with this class of compounds. The mechanistic basis for the greater sensitivity of monkeys to AP activation by 2′-MOE ASO was evaluated using purified human or monkey factor H protein. The binding affinities between a representative 2′-MOE ASO and either purified protein are similar. However, the IC50 of fluid-phase complement inhibition for monkey factor H is about 3-fold greater than that for human protein using either monkey serum or factor H–depleted human serum. Interestingly, there is a sequence variant in the monkey complement factor H gene similar to a single nucleotide polymorphism in humans that is correlated with decreased factor H protein function. These findings show that monkeys are more sensitive to 2′-MOE ASO–mediated complement activation than humans likely because of differences in factor H inhibitory capacity.